Early Complications After Mild to Moderate Ischemic Stroke and Impact on 3‐Month Outcome: The Multicenter Prospective Stroke Unit Plus Cohort Study - Jan Sobesky; Vince Istvan Madai; Sarah Zweynert; Carolin Malsch; Darius Guenther Nabavi; Heinrich J. Audebert; Christoph Kleinschnitz; Bruno Marcel Mackert; Bettina Schmitz; Frank Arne Wollenweber; Karl Georg Haeusler; Ian Wellwood; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Early stroke complications (ESCs) impair recovery and provide an important therapeutic target. Our multicenter prospective cohort study examined the prevalence and amount of poor outcomes attributable to ESCs. Methods and Results In patients with stroke, 16 ESCs were monitored by clinical assessment (“basic definition”) and by inclusion of laboratory values and clinical scales (“extended definition”). The association of complications with poor outcome (death or functional impairment: modified Rankin Scale score >3 or Barthel Index <60) at 3 months was analyzed using multiple logistic regression adjusted for stroke severity, age, and sex. Complications were stratified by their early treatment options, and average sequential population‐attributable fractions were estimated for treatable early complications. Of 1202 patients, outcome data were available for 1105 (91.9%; 43.0% women; mean age 68.3 years; baseline median National Institutes of Health Stroke Scale score on admission 3 points). Poor outcome was recorded for 100 patients (9.0%). By basic definition, recurrent stroke, fever, pneumonia, depression, urinary tract infection, and delirium were significantly associated with poor outcomes. The occurrence of 1 or more of these ESCs was associated with up to 19.6% of poor outcomes. By extended definition, urinary tract infection, depression, and delirium were significantly associated with poor outcomes. The occurrence of 1 or more of these ESCs was associated with up to 15.9% of poor outcomes. Conclusions In our cohort of patients with mild to moderate stroke, we identified a set of treatable ESCs with clinically relevant impact on outcome that may be targeted in future interventional trials. Registration URL: https://www.bfarm.de; Unique identifier: DRKS00004712.